(untitled) (West African Journal on Sustainable Development, 2024)
Workplace hostility is costly to the wellbeing of employees and detrimental to sustainable development of Nigerian organisations. Consequently, this study examined organizational frustration and psychological wellbeing as predictors of workplace hostility among non-teaching staff of Nnamdi Azikiwe University Awka, Anambra State. A total number of one hundred and twenty (120) non-teaching staff participated in the study. The participants were drawn from eight units of the administrative arm of the university using simple random sampling technique. The participants were aged between 25 to 50 years, with a mean age of 35.02 and a standard deviation of 6.46. The Workplace Hostility Scale, Organizational Frustration Scale and Ryff’s Scale of Psychological Wellbeing were instruments used to generate data for the study. The study tested three hypotheses. The first hypothesis stated that organizational frustration will significantly and positively predict workplace hostility and was accepted (β = .392, t= -3.580, p<.05). This result showed that organizational frustration was positively related to workplace hostility among workers. Hypothesis two which stated that psychological wellbeing will significantly and positively predict workplace hostility was rejected (β =-.009, t= -.086, P>.05). Hypothesis three which stated that organizational frustration and psychological wellbeing will both significantly predict workplace hostility was also rejected because the interaction between organizational frustration and psychological wellbeing did not positively predict workplace hostility. These findings have important implications for understanding the factors that contribute to hostility among workers and highlights the consequences of hostile behaviors in organizations. Therefore, it is recommended that employers prioritize the wellbeing of their workers and consider seeking psychological interventions to improve their working environment.